Ecotheology Values in English Education Materials - Forsiana, Yanita Ika (Critical Review of English-Arabic World Journal is an open-access journal published by the Language Development Unit, State Islamic University of Kiai Haji Achmad Siddiq, Jember, 2025)
Environmental problems such as deforestation, pollution, and climate change require educational strategies rooted in both ethical and spiritual values. This study explores the presence of ecotheological values in English education materials used in senior high schools in Indonesia. Employing a qualitative content analysis approach, the research examines English textbooks used nationally in Indonesia to identify themes related to environmental stewardship, ethical responsibility toward nature, and spiritual engagement with the environment. The findings reveal that environmental issues are only addressed in the second-grade English textbook, while the theological values here are largely implicit and rarely emphasized. Most texts present environmental content from scientific or practical perspectives, with limited integration of theological or ethical frameworks. This suggests an opportunity to foster ecological awareness and character development through English education. The study recommends a more intentional inclusion of ecotheological values in English language teaching to support holistic environmental education aligned with national character-building goals. By embedding ecotheological values, English learning can serve not only linguistic development but also moral and environmental consciousness. This integration may also strengthen the relevance of English education to local cultural and religious contexts.